Hemiarthroplasty for Femoral Neck Fractures in the Elderly: A Comparison of Cemented and Uncemented Femoral Stems. Issue 7 (July 2020) - DeRogatis, Michael J.; Piatek, Allison Z.; Jacob, Roshan; Kelly, Sean C.; Issack, Paul S.
Abstract : The incidence of displaced femoral neck fractures among elderly patients is increasing as the population ages. Historically, the preferred treatment for displaced femoral neck fractures in elderly patients has been hemiarthroplasty with use of cemented fixation of the implant. However, there is evidence that this technique may be associated with fat embolization and subsequent cardiopulmonary arrest in the early postoperative period. Cementing techniques are also associated with increased operative time when compared with cementless techniques. There is increasing evidence that, among elderly patients, the use of uncemented hemiarthroplasty has equivalent functional outcomes and overall mortality rates when compared with the use of hemiarthroplasty with cemented fixation. The main complication associated with uncemented hemiarthroplasty is intraoperative periprosthetic fracture.